Role of Circadian Clock Genes in Sudden Cardiac Death: A Pilot Study - Ikeda, Tomoya; Ishikawa, Takaki; Oritani, Shigeki; Michiue, Tomomi; Tani, Naoto (Journal of Hard Tissue Biology, 2017)
The present study deals with the circadian expression of clock genes in acute cardiac death to examine any correlation between clock gene expression and catecholamines. A total of 36 subjects, who died of acute ischemic heart disease (AIHD, n = 10), acute myocardial infarction (AMI, n = 11), and recurrent myocardial infarction (RMI, n = 15) and underwent autopsy within 2 days after death, were included in this study. The mRNA expression levels of the clock genes BMAL1, PER2, and REV-ERBα were determined in the post-mortem heart tissue. Catecholamine levels in blood obtained from the right heart were measured. Furthermore, the cellular localization of clock proteins was assessed by immunohistochemistry, and protein levels in the heart tissue were also measured by Western blotting. In our cases of AIHD death, BMAL1 and PER2 exhibited trimodal expression patterns; however, the trimodal expression pattern of PER2 was antiphasic to that of BMAL1. PER2 expression correlated with adrenaline and noradrenaline levels. In deaths from AMI, BMAL1 and PER2 exhibited antiphasic trimodal and bimodal expressions, respectively, and BMAL1 expression correlated with adrenaline and noradrenaline levels. In RMI, both BMAL1 and PER2 exhibited antiphasic unimodal expression patterns, which were not correlated with adrenaline and noradrenaline levels. REV-ERBα expression varied, and no correlations were found between dopamine levels and clock gene expression in any group. We concluded that catecholamine levels are decreased in AIHD and raised in AMI as a function of BMAL1 expression and that BMAL1 and PER2 modulate and suppress catecholamine levels respectively.